Analisis Internal Marketing Dalam Membangun Citra Perusahaan Lewat Optimalisasi Peran Receptionist Di Cordova Edupartment Semarang: Analisis Internal Marketing Dalam Membangun Citra Perusahaan Lewat Optimalisasi Peran Receptionist Di Cordova Edupartment Semarang - Tussifah, Hamidah; Farah Diba Aya Rosady; Aziizah, Silmina Nur; Marjany, Nawa (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The purpose of this study is to examine how the implementation of internal marketing helps improve company image by optimising the role of receptionists at Cordova Edupartment Semarang. Human resource management strategies known through internal marketing emphasise the importance of preparing employees as internal customers so that they can provide the best service to external customers. Receptionists, who serve as the front line of the company, play an important role in determining how customers first perceive the company. This study employs a qualitative methodology using observation, interviews, documentation, and hands-on practice to collect data. The results indicate that the implementation of internal marketing elements, such as training and development, supportive leadership, internal communication, and recruitment and compensation systems, can enhance the quality of receptionist services. Excellent service directly impacts customers' perceptions of the company. Therefore, through the important role of receptionists, internal marketing is an effective method for building and maintaining a company's reputation